An Approach to Knowledge Management in Construction Service – Oriented Architecture - Gromoff, Alexander; Kazantsev, Nikolay; (Stavenko), Julia Bilinkis (Procedia computer science, 2016)
Modern business driving requires agility in the reflecting changes of Service-oriented Enterprise Architecture (SoEA). For this purpose Subject-oriented Business Process Management (S-BPM) was used for facilitation of structured communication between process participants, process experts and resulted generation of collaborative business process. During such generation all necessary requirements for supporting resources (such as information, know-how, intellectual and professional skills, inputs and outputs, quality and operational risk limitations, moderation, control and monitoring) are taken into consideration using the operational knowledge of experts and project participants that act inside the predefined business area. The work results in updating the business model selecting business services from the virtual SOA torrent (that catches rated cloud services on the internet) and represents the basis for quickly adjustable “real-time” service-oriented enterprise architectures.